The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11104-021-05225-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in organic and inorganic phosphorus compounds as affected by long-term synthetic fertilisers and pig manure in arable soils

Abstract: was lower than on adding manure+superphosphate. Other monoester P compounds, typically related to microbial biomass and processes were highest on adding pig manure+urea. When adding superphosphate+urea+pig manure a reduction of these P compounds was observed as well as the highest accumulation of inositol hexakisphosphate (IHP). Synthetic fertilisers increased Olsen-P, orthophosphate and other monoester and total IHP and largely decreased soil pH. The addition of pig manure greatly increased the stereoisomers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Increases in other-monoester compounds in organic C-enriched cropped soils amended with exogenous organic C have been related to microbial biomass and processes (Li et al, 2022a). In the present study, levels of other-monoesters increased in the organic C-enriched layer of crop-growing soil and incubated plantfree soils.…”
Section: Effects Of Growing Crops In Compost-amended Soilssupporting
confidence: 54%
See 3 more Smart Citations
“…Increases in other-monoester compounds in organic C-enriched cropped soils amended with exogenous organic C have been related to microbial biomass and processes (Li et al, 2022a). In the present study, levels of other-monoesters increased in the organic C-enriched layer of crop-growing soil and incubated plantfree soils.…”
Section: Effects Of Growing Crops In Compost-amended Soilssupporting
confidence: 54%
“…However, the IHP in our soils was not related to the levels of microbial biomass or soluble C and it was not an important variable for the discrimination between C-enriched and C-depleted soils in the rst PCA axis, perhaps because of the IHP content in the compost itself. Indeed, higher abundances of IHP have been found during the composting process (Hashimoto et al, 2014) and after adding manures to soils (Li et al, 2022a).…”
Section: Effects Of Compost Amendmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pig manure could effectively alleviate soil acidification ( Bei et al, 2018 ); in the present study, the M treatment had the highest pH value. Pig manure is enriched with organic matter and nutrients including nitrogen, phosphorus, and potassium ( Ding et al, 2017 ; Li et al, 2022 ); thus our results indicated general improvements in soil fertility after 12 years of combined application of pig manure and chemical fertilizers on aeolian sandy soil.…”
Section: Discussionmentioning
confidence: 55%